Myelin-oligodendrocyte glycoprotein associated optic neuritis: a case report - Gowda, Medhini H.; Patel, Rithesh; Anwitha, G. Sri Sai (International Journal of Research in Medical Sciences, 2024)
The role of myelin-oligodendrocyte glycoprotein (MOG) in central nervous system (CNS) myelin and its association with optic neuritis. It emphasizes the importance of early detection and suitable diagnostic investigations for optic neuritis, a condition often linked to multiple sclerosis. A 65-year-old female with MOG-positive CNS demyelination, optic neuritis, and underlying conditions such as hypertension and type 2 diabetes mellitus. The patient’s clinical examination, diagnostic test results, and imaging findings are presented, including fundoscopy, 2D Echo, and magnetic resonance imaging (MRI) of the spine. The treatment chart outlines medications administered to the patient. It delves into challenges in identifying optic neuritis, emphasizing the significance of clinical-MRI phenotypes associated with MOG-associated disorders (MOGAD) and reliable laboratory assays for detecting MOG-IgG. It highlights the need for caution in interpreting positive MOG-IgG results and underscores the importance of follow-up for individuals with MOG-IgG seropositivity. The article also discusses various aspects of optic neuritis, including visual field impairments and retinal changes associated with anti-MOG antibodies. It emphasizes the importance of timely and accurate identification of MOGAD through anti-MOG antibody detection. It calls for standardized diagnostic criteria and the refinement of models to enhance understanding and therapeutic approaches for MOGAD. Overall, the article provides insights into the diagnosis, management, and challenges associated with MOG-related disorders.